Soil Biology Contribution on Agricultural Land Suitability Evaluation of Wet Tropical Megabiodiversity Regions - GITOSUWONDO, SUBOWO; SANTOSA, EDI; ANAS, ISWANDI (Indonesian Center for Agriculture Land Resource Development, 2010)
Indonesia is in the region